Titanic : legacy of the world's greatest ocean liner - Wels, Susan; Discovery Channel (Firm) ([Alexandria, VA] : Time-Life Books, 1997)
Provides details on the Titanic's construction, her wreck in 1912, and present-day exploration and salvage operations.
On the ocean floor / William F. Buckley, Jr. -- Titanic / John P. Eaton & Charles A. Haas -- Time of the Titanic -- Maiden voyage -- Terror at sea -- In search of the Titanic -- Anatomy of the disaster -- Trail of time.
"Discovery Channel."
Includes bibliographical references (p. 203) and index.
Keywords: Titanic (Steamship); Shipwrecks -- North Atlantic Ocean